A novel substituted derivative of sterol from marine actinomycetes Nocardiopsis alba MCCB 110 antagonistic to the aquaculture pathogen Vibrio harveyi. (August 2021) - Sunish, K.S.; Sreedharan, Prathapan; Daniel, Sobhi; Biji, Mathew; Rosamma, Philip; Sukumaran, Vrinda; Mohandas, A.; Singh, I.S. Bright
Abstract: In an attempt to screen antagonistic microorganisms from marine environment for the management of bacterial pathogens in aquaculture, an isolate of actinomycete MCCB 110 was segregated based on its comparatively higher inhibitory property on Vibrio harveyi (MCCB 111) and profound luminescent inhibition. Based on the culture characteristics, cell wall fatty acid profile and the nucleotide sequence of the 16S rRNA gene (1495 bp), the isolate was identified as Nocardiopsis alba. Solvent extraction of the fermentation broth followed by TLC and HPLC analyses resulted in the isolation of a major fraction active against luminescent Vibrio harveyi . Partial characterization of this bioactive fraction based on spectroscopic data obtained from FT-IR, UV, MS-MS and 1 H NMR analyses identified it as a substituted derivative of sterol, and was recognized to differ from those reportedly produced by the same genus. The fraction was not toxic to VERO cell line and shrimp haemocytes up to 1000 ppm tested. The study demonstrated the potential of the putative probiotic Nocardiopsis alba (MCCB 110) and its novel extra-cellular bioactive product in the management of Vibrio harveyi in aquaculture. Highlights: This study demonstrated the potential of a putative probiotic Nocardiopsis alba MCCB 110 in aquaculture. Nocardiopsis alba was identified based on cultural characteristic, cell wall fatty acid profile and 16S rRNA gene. Exhibited higher inhibitory property and profound luminescent inhibition against the aquaculture pathogen Vibrio harveyi . The active fraction was identified as a novel substituted derivative of sterol with a molecular weight of 453.